2015
DOI: 10.1016/j.cels.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Modular Viral Scaffolds for Targeted Bacterial Population Editing

Abstract: SUMMARY Bacteria are central to human health and disease, but existing tools to edit microbial consortia are limited. For example, broad-spectrum antibiotics are unable to accurately manipulate bacterial communities. Bacteriophages can provide highly specific targeting of bacteria, but assembling well-defined phage cocktails solely with natural phages can be a time-, labor- and cost-intensive process. Here, we present a synthetic-biology strategy to modulate phage host ranges by engineering phage genomes in Sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
298
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(302 citation statements)
references
References 39 publications
(43 reference statements)
3
298
0
1
Order By: Relevance
“…By delivering the CRISPR-Cas RNA-guided nuclease system with phages, designated strains can be selectively eliminated based on their genetic content [47]. Furthermore, phage host ranges can be modularly engineered by swapping phage tail components [48]. Altering phage populations represents another avenue for microbiome modulation; exposing the gut microbiome to antibiotics alters its associated virome and ecological networks [49].…”
Section: Contemporary Methods For In Situ Microbiome Engineeringmentioning
confidence: 99%
“…By delivering the CRISPR-Cas RNA-guided nuclease system with phages, designated strains can be selectively eliminated based on their genetic content [47]. Furthermore, phage host ranges can be modularly engineered by swapping phage tail components [48]. Altering phage populations represents another avenue for microbiome modulation; exposing the gut microbiome to antibiotics alters its associated virome and ecological networks [49].…”
Section: Contemporary Methods For In Situ Microbiome Engineeringmentioning
confidence: 99%
“…The authors also demonstrated that gene swapping between more distant phage relatives could enable a genetically modified E. coli phage to target Klebsiella bacteria and a genetically modified Klebsiella phage to target E. coli bacteria (Table 1). This work further showed that synthetic phage cocktails composed of phages with the same scaffold but different tail components can be used to target mixed bacterial populations and to selectively remove specific bacterial species from them (85).…”
Section: Engineered Phages With Shifted or Broadened Host Rangesmentioning
confidence: 87%
“…Phage genomes assembled, modified, and propagated in yeast have been isolated and introduced into bacteria to generate functional phage particles (84). This technique has been used to capture and genetically modify the genomes of the coliphages T3 (38,208 bp) and T7 (39,937 bp) (84,85) as well as the Klebsiella phage K11 (41,181 bp) (85). It was further used to capture and archive the genome of fully refactored phage ⌽X174 (6,302 bp) (86).…”
Section: Yeast-based Assembly Of Phage Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel methods for selective microbiome modulation, including antibiotic treatment [93], bacteriophage therapy [94-96], dietary supplementation [87], fecal microbiota transplantation [66, 97], and probiotic microbial interventions [88] all provide opportunities to specifically control the composition and/or function of the gut microbial community (Box 3).…”
Section: Advancements In Gut Microbiome Modulation and Host Healthmentioning
confidence: 99%